A semi-analytical study considering Christov-Cattaneo flux model and Stephan blowing effects: Thermally radiative flow of NaAlg based ternary hybrid nanoliquid - Mostafa Mohamed Okasha; Ahmed Babeker Elhag; Munawar Abbas; Shirin Shomurotova; Jihad Younis; Mustafa Bayram; Abdullah A. Faqihi; Abdulhadi A. Altherwi; Ibrahim Mahariq; Muhammad Shafique (Case Studies in Thermal Engineering)
The outcome of heat radiation and Stephan blowing on Marangoni convective flow of ternary hybrid nanofluid over isothermal permeable non-linearly sheet with Christov-Cattaneo flux model and heat generation. It is particularly useful in microfluidic devices, electronic cooling, solar collectors, and biomedical applications where precise thermal control is important. The ternary hybrid nanofluid enhances heat transmission efficiency, while the Christov-Cattaneo model ensures more accurate prediction of non-Fourier heat conduction in high-speed and microscale systems. This study also aids in the design of materials processing, coating technologies, and energy systems involving thermal gradients and surface tension effects. The similarity quantities were used to modify the governing equations for this fluid flow with a concentrate on non-linear ODEs. The problem's mathematical basis is demonstrated by velocity, temperature, and concentration visualizations. The temperature profiles rise in parallel with the enhancement of the thermal radiation of limitations. With rising thermal and solutal distribution values, the concentration and thermal profiles are rising as well.